RVSec : Runtime verification methods for high precision detection of cryptography API misuse - Torres, Adriano Rodrigues Figueiredo (2022)
Dissertação (Mestrado em Informática) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, Brasília, 2022.